Biomass-mediated synthesis of Cu-doped TiO2 nanoparticles for improved-performance lithium-ion batteries - Kashale, Anil A.; Dwivedi, Pravin K.; Sathe, Bhaskar R.; Shelke, Manjusha V.; Chang, Jia-Yaw; Ghule, Anil V. (ACS Omega, 2018)
Pure TiO2 and Cu-doped TiO2 nanoparticles are synthesized by the biomediated green approach using the Bengal gram bean extract. The extract containing biomolecules acts as capping agent, which helps to control the size of nanoparticles and inhibit the agglomeration of particles. Copper is doped in TiO2 to enhance the electronic conductivity of TiO2 and its electrochemical performance. The Cu-doped TiO2 nanoparticle-based anode shows high specific capacitance, good cycling stability, and rate capability performance for its envisaged application in lithium-ion battery. Among pure TiO2, 3% Cu-doped TiO2, and 7% Cu-doped TiO2 anode, the latter shows the highest capacity of 250 mAh g(-1) (97.6% capacity retention) after 100 cycles and more than 99% of coulombic efficiency at 0.5 A g(-1) current density. The improved electrochemical performance in the 7% Cu-doped TiO2 is attributed to the synergetic effect between copper and titania. The results reveal that Cu-doped TiO2 nanoparticles might be contributing to the enhanced electronic conductivity, providing an efficient pathway for fast electron transfer.